Discrete geometry for computer imagery : 20th IAPR International Conference, DGCI 2017, Vienna, Austria, September 19-21, 2017, Proceedings /: 20th IAPR International Conference, DGCI 2017, Vienna, Austria, September 19-21, 2017, Proceedings. (2017) - Unknown
No abstract available